2020
DOI: 10.4103/jfmpc.jfmpc_795_20
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular pressure and tear production changes in pregnant women at term pregnancy and immediate post-partum: A pilot study

Abstract: Aim: To study the intraocular pressure (IOP) and tear production changes in uncomplicated pregnant women at term pregnancy and immediate postpartum. Materials and methods: The patients admitted in the Department of Obstetrics and Gynaecology for delivery were included in the study. A total of 106 participants who were at term uncomplicated pregnancy were selected according to the inclusion and exclusion criteria. They were subjected to type 1 Schirmer's testing and intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Multiple published studies have reported that IOP is statistically lower in pregnant women compared to healthy non-pregnant women [ 24 - 26 ]. We noted similar findings in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple published studies have reported that IOP is statistically lower in pregnant women compared to healthy non-pregnant women [ 24 - 26 ]. We noted similar findings in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have postulated that IOP reduction can be due to various mechanisms. High progesterone levels during pregnancy can cause an increase in the fluid outflow from the eye and a reduction in the episcleral venous pressure resulting from decreased total systemic vascular resistance [ 16 , 18 , 24 ]. Wang et al and Shrinkhal et al have added that human chorionic gonadotrophin, nitric oxide, endothelin-I, eicosanoids, and relaxin also play a role in the reduction of IOP in pregnancy [ 9 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hormonal changes during pregnancy can lead to various physiological changes and affect the eyes. 21,22 Various ocular changes take place during pregnancy because of increased hormones, which include alterations in tear film composition and thickness, cornea sensation and refractive power. 22 Dry eye has been reported to be common in pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…For OSDI, the degree of dryness was categorised as normal (0-12), mild (13)(14)(15)(16)(17)(18)(19)(20)(21)(22), moderate (23)(24)(25)(26)(27)(28)(29)(30)(31)(32), and severe (33-100). 9 The PRT test involved the use of a cotton thread that contained a potential of hydrogen (pH) indicator.…”
Section: Introductionmentioning
confidence: 99%
“…Hormone receptors have been demonstrated in the human cornea [4]; thus, the biological functions of corneal cells may be influenced through direct interaction with specific hormones during this period. Many past studies have reported pregnancy-induced changes in the eyes, including changes in the central corneal thickness [5], intraocular pressure [6], biomechanics in the cornea [7], tear production changes [6], etc., and some existing ocular diseases are exacerbated or new pathology develops in pregnant women, such as diabetic retinopathy [8], and central serous chorioretinopathy [9]. Due to individual variability, the results of ocular changes induced by pregnancy vary.…”
Section: Introductionmentioning
confidence: 99%